Advanced human mucosal tissue models are needed to improve preclinical testing of vaccines. - David Komla Kessie (Public Library of Science (PLoS), 2021)
Many vaccine candidates with promising results in preclinical testing fail in human trials. New complex human tissue models have the potential to improve the predictability of vaccine safety and efficacy in human clinical trials.